(untitled) (Applied Biological Research, 2023)
This experiment was conducted to assess the effect of soy isoflavones (daidzein and genistein) on oestradiol concentration in the blood plasma of layer chicken. Group I birds were fed with regular standard maize-soybean meal based diet as per BIS 2007 specification containing 22.5% soybean meal, group II with standard layer diet without soybean meal (BIS, 2007) and group III was supplemented with soy isoflavones enriched diet (0.5 g dried hypocotyl sprout of soybean 100 g-1feed) for a period of 56 days. The levels of free isoflavones in soybean meal and blood plasma derived through β-glucuronidase treatment were quantified using liquid chromatography–mass spectrometry (LC-MS) technique. The genistein levels were 2.89 ± 0.02,1.84 ± 0.13, and 3.25 ± 0.04 µg g-1, while daidzein levels were 1.15 ± 0.26, 0.20 ± 0.03, and 2.40 ± 0.09 µg g-1, respectively, in feeds of groups I, II, and III. The mean genistein and daidzein content in blood plasma was found higher for group III birds compared to other two treatment groups. After feeding trial, plasma concentration of oestradiol 17β was estimated by using radioimmune assay (RIA) technique which was found higher for group II (673.45 ± 7.69 pg mL-1) as compared to the group I (979.21 ± 12.57 pg mL-1) and III (314.23 ± 6.34 pg mL-1). The study showed that the higher amount of isoflavones in feed could lower endogenous production of oestradiol from ovaries.